Efficacy of insecticides through contact and oral uptake towards four Agriotes wireworm species under controlled conditions. (18th April 2013) - van, K.; Huiting, H. F.; Wilhelm, R.; Heger, M.; Ester, A.
<x xml:space="preserve">Abstract</x> Wireworms of Agriotes lineatus, A. obscurus, A. sputator and A. sordidus were exposed to insecticide treated soil using two different control methods. One method consisted of a spray application of insecticides at doses of 50, 100, 200, and 300 g a.i. per ha. The other method consisted of a bait treatment at doses of 0.01, 0.1, 1, and 10 g a.i. per ha. Four insecticides were tested: fipronil and the neonicotinoids thiamethoxam, imidacloprid and clothianidin. In the soil treatment trial, chlorpyrifos was added as a reference treatment. The two test methods were conducted at different dates on the various species, but in equally controlled conditions. Mortality was observed after one and two (bait treatment) or three (soil treatment) weeks of exposure. Fipronil was highly lethal to each of the wireworm species tested, regardless of the method used. In general, mortality was higher compared to the neonicotinoids tested, the latter showing low or no mortality at the given dose and exposure variants. Applying fipronil in a bait formulation may decrease the amount of active ingredient per ha considerably, therefore baits may have important environmental benefits.